2017
DOI: 10.1073/pnas.1705739114
|View full text |Cite
|
Sign up to set email alerts
|

TPC2 polymorphisms associated with a hair pigmentation phenotype in humans result in gain of channel function by independent mechanisms

Abstract: Two-pore channels (TPCs) are endolysosomal cation channels. Two members exist in humans, TPC1 and TPC2. Functional roles associated with the ubiquitously expressed TPCs include VEGF-induced neoangiogenesis, LDL-cholesterol trafficking and degradation, physical endurance under fasting conditions, autophagy regulation, the acrosome reaction in sperm, cancer cell migration, and intracellular trafficking of pathogens such as Ebola virus or bacterial toxins (e.g., cholera toxin). In a genome-wide association study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 42 publications
7
63
0
Order By: Relevance
“…Advances in molecular biology have enabled cell type-specific conditional TPC1 and TPC2 KO cells and animals, allowing the study of the distinctive roles of TPC1 and TPC2. In addition, a recent report revealed that two variants of point mutations on human TPC2 are linked with alteration of hair pigmentation [ 93 ]. Therefore, our understanding of TPCs would also be broadened by studying data from national and international biobanks and investigating clinical symptoms or tissue samples of individuals identified with naturally occurring mutations on human TPC1 and TPC2 (see Outstanding Questions).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Advances in molecular biology have enabled cell type-specific conditional TPC1 and TPC2 KO cells and animals, allowing the study of the distinctive roles of TPC1 and TPC2. In addition, a recent report revealed that two variants of point mutations on human TPC2 are linked with alteration of hair pigmentation [ 93 ]. Therefore, our understanding of TPCs would also be broadened by studying data from national and international biobanks and investigating clinical symptoms or tissue samples of individuals identified with naturally occurring mutations on human TPC1 and TPC2 (see Outstanding Questions).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…While TPC2 sensitivity to ATP requires mTORC1 kinase activity, the mTOR target site on TPC2 remains uncharacterised. Recently however, a widely distributed human TPC2 gain-of-function polymorphism (G734E) was linked to decreased ATP sensitivity [34]. This could provide a stepping stone to further elucidate the exact mechanism of mTORC1-dependent TPC regulation.…”
Section: Tpcs and Mtormentioning
confidence: 99%
“…Symptoms of the Menkes patients vary but include abnormalities in hair and skin [62]. TPC2 defect leads to abnormalities of melanin production and pigmentation [63]; however, their corresponding disease was not reported (Table 1). Here, we summarize the current knowledge of the ion transport proteins-their physical properties, biochemical functions, physiological roles and pathological effects in melanosomes.…”
Section: Ion Transport Proteins In Melanogenesismentioning
confidence: 99%
“…Meanwhile, Bellono et al demonstrated the PI(3,5)P 2 activates TPC2-mediated Na + -selective conductance [126]. The response to PI(3,5)P 2 is further observed in a TPC2-expressing endolysosome models [63]. Nevertheless, loss of TPC2 clearly affects melanosomal pH and size, and melanin production.…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%